Arbitration agrement and standard form contracts: judgement number 409/2017 of 27th june of the Spanish Supreme Court - Blanco García, Ana Isabel; Quinzá Redondo, Pablo (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Judgment number 408/2017 of the Spanish Supreme Court deals with the potential application of an arbitration agreement in the case of a standard form contract. In particular, it focuses on the jurisdiction of the judge to interpret the arbitration agreement and on the questions that are covered by the arbitration agreement itself.